Static dan Dynamic Stretching Exercise Meningkatkan Kemampuan Sprint pada Pemain Sepak Bola - Ryan Hidayatullah; Nurwijayanti Nurwijayanti; Novita Anna Anggraeni; Indasah Indasah; Byba Melda Suhita (FORIKES, 2022)
Football is one of the sports that is in great demand by the public. Early childhood sports injuries can occur due to various things while undergoing training or during matches, such as physical training, techniques and tactics that are not programmed properly. Elasticity plays a role as an important factor that affects the increase in speed. Muscle elasticity must be maintained in order to produce good speed. The purpose of this study was to analyze the benefits of static and dynamic stretching exercises to increase the speed (sprint) of soccer players. This research was carried out for 6 weeks with the intensity of training 3 times a week from April 2022 to May 2022, involving 27 Paramed FC soccer players. The measuring instrument used to measure running speed is the 30 Meter Sprint Test. In the Static Stretching (K1), Dynamic Stretching (K2) and Control Group (K3) treatment groups, the pretest-posttest values showed that the data were normally distributed (p > 0.05). In the pretest-posttest after the Static Stretching (K1) treatment, Dynamic Stretching (K2) Control Group (K3) obtained a p value <0.05, which means that there is a significant difference between the pretest and posttest. It can be concluded that the interventions provided are effective in increasing sprint ability in soccer players.Keywords: static stretching; dynamic stretching; sprints; football ABSTRAK Sepak bola menjadi salah satu cabang olahraga yang sangat diminati oleh masyarakat. Cedera olahraga sepak bola usia dini dapat terjadi karena berbagai hal saat menjalani latihan maupun saat bertanding, seperti latihan fisik, teknik dan taktik yang tidak terprogram dengan baik. Elastisitas memegang peranan sebagai faktor penting yang berpengaruh terhadap peningkatan kecepatan. Elastisitas otot harus dipelihara agar dapat menghasilkan kecepatan yang baik. Tujuan penelitian ini adalah menganalisis manfaat latihan static dan dynamic stretching untuk meningkatkan kemampuan kecepatan (sprint) pada pemain sepak bola. Penelitian ini dilaksanakan selama 6 minggu dengan intensitas latihan 3 kali dalam seminggu pada bulan April 2022 sampai Mei 2022, dengan melibatkan 27 pemain sepak bola Paramed FC. Alat ukur yang digunakan untuk mengukur kecepatan lari adalah 30 Metre Sprint Test. Pada kelompok perlakuan Static Stretching (K1), Dynamic Stretching (K2) dan Control Group (K3) nilai pretest-posttest menunjukkan data terdistribusi normal (p >0,05). Pada pretest-posttest setelah dilakukan perlakuan Static Stretching (K1), Dynamic Stretching (K2) Control Group(K3) didapatkan nilai p <0,05, yang bermakna bahwa terdapat perbedaan yang signifikan antara pretest dan posttest. Dapat disimpulkan bahwa intervensi yang diberikan efektif untuk meningkatkan kemampuan sprint pada pemain sepak bola.Kata kunci: static stretching; dynamic stretching; sprint; sepakbola